Toward enhanced activity of a graphitic carbon nitride-based electrocatalyst in oxygen reduction and hydrogen evolution reactions via atomic sulfur doping - Pei, Zengxia; Zhao, Jingxiang; Huang, Yan; Huang, Yang; Zhu, Minshen; Wang, Zifeng; Chen, Zhongfang; Zhi, Chunyi (Journal of materials chemistry. A, Materials for energy and sustainability, 2016)
Atomic doping has always been demonstrated as a feasible way to effectively alter the catalytic properties of metal-free electrocatalysts. Herein, we report the first experimental and theoretical investigation regarding the influence of sulfur doping on the activity of a carbon nitride (C 3 N 4 )-based electrocatalyst in the oxygen reduction reaction (ORR) and hydrogen evolution reaction (HER). It is found that the sulfur dopant within the mesoporous carbon-supported C 3 N 4 motif can remarkably boost its ORR activity, which rivals that of commercial Pt/C yet with better cross-over tolerance and durability, while the HER performance of the composite catalyst is superior than most other reported metal-free electrocatalysts and is even comparable to the most active non-noble metal-based HER materials. Theoretical calculations further reveal that the excellent activity of the doped composite stems from the high charge and spin densities in the C 3 N 4 motif as well as altered competent adsorption energies of reaction intermediates via the atomic sulfur doping. The results in this work feature a facile and effective approach for engineering a high performance C 3 N 4 -based electrocatalyst, which may also enlighten the designing and fabrication of other metal-free materials as next-generation electrocatalysts.